Efficiency achievement in water supply systems—A review - Coelho, B.; Andrade-Campos, A. (Renewable & sustainable energy reviews, 2014)
The worldwide water supply represents a significant portion of the global energy consumption. This energy consumption, related to the collection, treatment and transportation of water, entails a large amount of costs. However, these costs are liable to be minimised with and/or without reduction on energy consumption. The purpose of this paper is to provide a review about measures and methods to achieve water supply systems efficiency. The paper summarises and compares previous investigations in order to provide the state-of-the-art to the reader. Measures with and without investment in order to reduce costs and energy consumption are presented. The paper also explores the use of hydraulic simulation and optimisation strategies in water supply systems, involving topics such as demand prediction, networks design, pumps operation, real-time operations and renewable energy production. Although the great advances in the area, there are unexplored (or poorly explored) methodologies that can be tested and maybe applied in a large number of water systems. There are also some important issues, mentioned in this paper, which must be considered in order to attend specific requirements of the water industries.